Evaluating The Impact of ESG Rating on Corporate Performance: Study at PT Great Giant Pineapple - Fisena Hardiyanto; Indra Ardiyanto (International Journal Labs, 2025)
The implementation of Environmental, Social, and Governance (ESG) principles has become a strategic factor in the management of modern corporations, particularly in the agribusiness sector, which is often challenged by environmental and social issues. This study focuses on PT Great Giant Pineapple (PT GGP), one of the largest horticultural companies in Indonesia, which has received a positive ESG rating. It aims to explore how ESG ratings influence managerial decision-making dynamics, organizational communication strategies, and both financial and non-financial corporate performance. The research adopts a constructivist paradigm and a qualitative case study approach. Data were collected through observation, in-depth interviews with PT GGP's internal managers, and document analysis, including sustainability reports and the company's external communication materials. This study employs the Organizational Identity Theory (Albert & Whetten, 1985), through which ESG ratings are understood to be internalized and reflected in the organization's identity—particularly in how the company defines itself in terms of sustainability and social responsibility. Additionally, the Institutional Theory (Scott, 2021) is applied to understand ESG ratings as a form of legitimacy required by global stakeholders. Overall, the findings indicate that ESG ratings are internalized by PT GGP's management not merely as administrative compliance tools, but as instruments of legitimacy and strategic compasses in decision-making processes. ESG serves as a framework for shaping the company's long-term strategies, especially in sustainable operations and stakeholder relations. PT GGP's ESG communication strategy has proven adaptive, integrating informing, responding, and involving approaches that build public credibility and trust in the company's sustainability commitment. The ESG rating also impacts corporate performance, where increased operational efficiency, consumer loyalty, and investor appeal serve as non-financial indicators contributing to corporate reputation and value. However, the study also identifies challenges such as the lack of standardized ESG indicators and the risk of greenwashing, which continue to hinder the full optimization of ESG's strategic value. These findings reinforce legitimacy theory, which posits ESG as a tool for articulating the values and norms society expects from corporations and as part of a communication strategy to maintain social legitimacy amid rising sustainability awareness. This research contributes theoretically to the development of sustainability-based strategic communication studies and offers practical implications for companies aiming to integrate ESG as part of their long-term corporate transformation.